A content comparison of 4 commonly used adult upper limb amputee outcome measurements with application of the refinements of ınternational classification of functioning, disability, and health linking rules - Hatice Gül; Senem Demirdel; Tezel Yıldırım Şahan; Bahar Anaforoğlu Külünkoğlu; Sevilay Seda Baş; Senay Çerezci Duygu; Murat Ali Çınar; Hilal Keklicek; Kezban Bayramlar; Çınar, Murat Ali (My University, 2023)
Introduction: The application of the refinements of linking rules to the outcome measurement methods provides an opportunity to obtain information concerning what the available instruments actually measure and how the instrument measures certain outcomes. The purpose of the study was to analyze the content of 4 commonly used upper limb amputee scales using the refined International Classification of Functioning, Disability, and Health (ICF) linking rules. Methods: The Upper Extremity Functional Status module of the Orthotics and Prosthetics User Survey (OPUS-UEFS), Trinity Amputation and Prosthesis Experience Scales, Southampton Hand Assessment Procedure (SHAP), and Quick Disability of the Arm, Shoulder, and Hand were analyzed by 2 health professionals for a content comparison based on ICF categories. The Kappa statistic was used to calculate the degree of agreement between 2 professionals. Results: The scale questions were linked with 43 different ICF codes in this study. Trinity Amputation and Prosthesis Experience Scale addresses all ICF domains. All items of SHAP and most items of OPUS-UEFS were linked to the activity-participation domain. Quick Disability of the Arm, Shoulder, and Hand items were linked with activity-participation and body function domains. The perspectives of OPUS-UEFS and SHAP are descriptive. The perspectives of Quick Disability of the Arm, Shoulder, and Hand were descriptive and appraisal. The perspectives of Trinity Amputation and Prosthesis Experience Scale subscales were descriptive, appraisal, and needs or dependency. Estimated kappa values ranged from 0.44 to 0.91 for ICF codes. Conclusions: Most concepts in the scales were frequently linked to the activity-participation domain. We think that the results of this study will be a useful guide to clinicians and researchers in selecting relevant and appropriate outcome measurements for upper limb amputee rehabilitation.